2011
DOI: 10.1515/jpm.2011.084
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping pre-clerkship years in reproductive medicine education

Abstract: The educational program of the Paul L. Foster School of Medicine in El Paso, Texas integrates the basic and clinical sciences and organizes them according to the organ-system based units. The reproduction unit focuses on human reproduction, pregnancy and illnesses associated with the female genital tract and breast. The sequence of 13 clinical presentations is structured so that the concepts developed during the study of one topic lays down a foundation for subsequent topics. Students are provided with a brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Thirty‐one studies reported student responses about their knowledge on, perceptions of, or experiences with, sexual and reproductive health teaching 2–5,8,9,13–15,18,19,24,32–36,38–41,43,44,46–49,51–53,55,56 . Five studies provided insights from medical educators about their experiences with contraception and abortion education 7,23,48,49,53 . Two qualitative studies explored student perspectives on sexual and reproductive health education 19,29 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐one studies reported student responses about their knowledge on, perceptions of, or experiences with, sexual and reproductive health teaching 2–5,8,9,13–15,18,19,24,32–36,38–41,43,44,46–49,51–53,55,56 . Five studies provided insights from medical educators about their experiences with contraception and abortion education 7,23,48,49,53 . Two qualitative studies explored student perspectives on sexual and reproductive health education 19,29 …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies assessed the sexual and reproductive health education of preclinical students—those in their first or second year of medical school 3,8,18,27,30,32,33,38,48 . Twenty‐one USA studies assessed clinical students during their third year clerkships 2,4,5,9,11–17,19,21–23,26,28,31,40,49,55 . Two studies assessed sexual and reproductive health education from all years in medical school through surveys of faculty with knowledge of the curriculum 7,53 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations